Artificial Intelligence in Healthcare: Transforming the Future of Medicine (International Journal of Latest Technology in Engineering Management & Applied Science, 2025)
Abstract: Healthcare is revolutionized by the unimaginable speed with which AI has evolved. The AI technologies, in particular, are at the forefront in diagnostics, personalization, and the simplification of administrative and R&D processes in the pharmaceutical industry. The investigation discusses the health care applications and advantages along with the problems and ethical issues that are traits of AI systems. Between major case studies and new strides in AI, technology is making health outcomes better while it is protecting patients' privacy, stopping biases, and reducing the need for human intervention.